Structural Argument and Pragmatic Analysis on DUA SISI Talkshow - Alma Alqarana Lubis (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2022)
This study deals with the structural argument and pragmatic analysis on Dua Sisi Talk Show. The objectives of the study were to analyze the argument structures of the speakers on Dua Sisi Talk Show, to investigate the speakers’ ways in delivering arguments and to  find out the dominant types of speech act used by the speakers on Dua Sisi Talk Show. This study applied a descriptive qualitative method to analyze the data. The data were the utterances presented by the speakers on Dua Sisi Talk Show. The technique of data analyzing was from the data reduction, data display, and conclusion drawing. The research finding showed that there were 32 arguments found in this research which consist of 13 standard arguments and 19 non-standard arguments. Furthermore, there were 22 arguments categorized as locutionary acts, 4 arguments categorized as illocutionary acts, and 6 arguments categorized as perlocutionary acts based on Austin’s theory. Locutionary act was the dominant type of speech acts found on Dua Sisi Talk Show.